2015
DOI: 10.1186/s40170-015-0129-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of glioma patients with ketogenic diets: report of two cases treated with an IRB-approved energy-restricted ketogenic diet protocol and review of the literature

Abstract: BackgroundBased on the hypothesis that cancer cells may not be able to metabolize ketones as efficiently as normal brain cells, the ketogenic diet (KD) has been proposed as a complementary or alternative therapy for treatment of malignant gliomas.Case presentationWe report here our experience in treating two glioma patients with an IRB-approved energy-restricted ketogenic diet (ERKD) protocol as monotherapy and review the literature on KD therapy for human glioma patients. An ERKD protocol was used in this pil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
0
9

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(118 citation statements)
references
References 19 publications
(23 reference statements)
2
104
0
9
Order By: Relevance
“…It was consistently reported that patients undergoing the KD presented with reduced blood glucose levels and beneficial therapeutic responses, including the transient disappearance of the brain tumor tissue (29)(30)(31). Thus, these case reports, along with numerous anecdotal observations, presented encouraging signs of metabolic reprogramming by the KD, along with the increased efficacy of standard of care treatment for malignant glioma (23,29).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…It was consistently reported that patients undergoing the KD presented with reduced blood glucose levels and beneficial therapeutic responses, including the transient disappearance of the brain tumor tissue (29)(30)(31). Thus, these case reports, along with numerous anecdotal observations, presented encouraging signs of metabolic reprogramming by the KD, along with the increased efficacy of standard of care treatment for malignant glioma (23,29).…”
Section: Introductionmentioning
confidence: 81%
“…It has been postulated that a ketogenic diet, i.e., a diet consisting of high fat, low carbohydrates and adequate protein, may be useful in the treatment of brain tumors (25)(26)(27)(28)(29)(30)(31). The present study was conducted to assess the therapeutic efficacy and safety of a KD concomitant with intranasal perillyl alcohol as a novel therapeutic strategy for recurrent GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Poor compliance was associated with the KD due to poor palatability [34,36]. Henderson et al reported a higher rate of diarrhoea in the ketogenic diet group compared to the placebo group however this was not discussed in the other studies [27].…”
Section: Adverse Effects and Issues Related To Ketosismentioning
confidence: 86%
“…Schwartz et al investigated whether the oral KD could alter glioma progression in two adult male patients with Glioblastoma Multiforme (GBM) [34]. Both patients had advanced posterior GBM and had already received surgery, radiotherapy and chemotherapy.…”
Section: Intracranial Neoplasmsmentioning
confidence: 99%
See 1 more Smart Citation